Sensitivity of joint atmospheric-terrestrial water balance simulations to soil representation: Convection-permitting coupled WRF-Hydro simulations for southern Africa - Zhenyu Zhang; Patrick Laux; Jussi Baade; Joël Arnault; Jianhui Wei; Xuejin Wang; Shasha Shang; Toby Marthews; Christiane Schmullius; Harald Kunstmann (Agricultural and Forest Meteorology, 2024)

Impact of alternative soil data sources on the uncertainties in simulated land-atmosphere interactions - Zhenyu Zhang; Patrick Laux; Jussi Baade; Joël Arnault; Jianhui Wei; Xuejin Wang; Yukun Liu; Christiane Schmullius; Harald Kunstmann (Agricultural and Forest Meteorology, 2023)

Satellitenüberwachung der Bewegungen der Möhnestaumauer - Jannik Jänichen; Clémence Dubois; Christiane Schmullius; Jussi Baade; Volker Bettzieche; Katja Last (WASSERWIRTSCHAFT, 2022)

Linking scales and disciplines: an interdisciplinary cross-scale approach to supporting climate-relevant ecosystem management - Christian Berger; Mari Bieri; Karen Bradshaw; Christian Brümmer; Thomas Clemen; Thomas Hickler; Werner Leo Kutsch; Ulfia A. Lenfers; Carola Martens; Guy F. Midgley; Kanisios Mukwashi; Victor Odipo; et al. (Climatic Change, 2019)

Applying regularized logistic regression (RLR) for the discrimination of sediment facies in reservoirs based on composite fingerprints - Bastian Reinwarth; Jordan K. Miller; Christoph Glotzbach; Kate M. Rowntree; Jussi Baade (Journal of Soils and Sediments, 2017)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Plant diversity positively affects short‐term soil carbon storage in experimental grasslands - SIBYLLE STEINBEISS; HOLGER BEßLER; CHRISTOF ENGELS; VICKY M. TEMPERTON; NINA BUCHMANN; CHRISTIANE ROSCHER; YVONNE KREUTZIGER; JUSSI BAADE; MAIKE HABEKOST; GERD GLEIXNER (Global Change Biology, 2008)
Increasing atmospheric CO 2 concentration and related climate change have stimulated much interest in the potential of soils to sequester carbon. In ‘The Jena Experiment’, a managed grassland experiment on a former agricultural field, we investigated the link between plant diversity and soil carbon storage. The biodiversity gradient ranged from one to 60 species belonging to four functional groups. Stratified soil samples were taken to 30 cm depth from 86 plots in 2002, 2004 and 2006, and organic carbon contents were determined. Soil organic carbon stocks in 0–30 cm decreased from 7.3 kg C m −2 in 2002 to 6.9 kg C m −2 in 2004, but had recovered to 7.8 kg C m −2 by 2006. During the first 2 years, carbon storage was limited to the top 5 cm of soil while below 10 cm depth, carbon was lost probably as short‐term effect of the land use change. After 4 years, carbon stocks significantly increased within the top 20 cm. More importantly, carbon storage significantly increased with sown species richness (log‐transformed) in all depth segments and even carbon losses were significantly smaller with higher species richness. Although increasing species diversity increased root biomass production, statistical analyses revealed that species diversity per se was more important than biomass production for changes in soil carbon. Below 20 cm depth, the presence of one functional group, tall herbs, significantly reduced carbon losses in the beginning of the experiment. Our analysis indicates that plant species richness and certain plant functional traits accelerate the build‐up of new carbon pools within 4 years. Additionally, higher plant diversity mitigated soil carbon losses in deeper horizons. This suggests that higher biodiversity might lead to higher soil carbon sequestration in the long‐term and therefore the conservation of biodiversity might play a role in greenhouse gas mitigation.